Utilizing hydrolysis and acidification via liquid fraction of digestate (LFD-HA) for methane production enhancement of corn straw: Physicochemical and microbial community characterization. (1st December 2021) - Liu, Yue; Gong, Hui; He, Shuting; Shi, Chuan; Yuan, Hairong; Zuo, Xiaoyu; Li, Xiujin
Abstract: The effectiveness of hydrolysis and acidification via liquid fraction of digestate (LFD-HA) strategy on enhancing methane production of corn straw (CS) were explored in this study. A post-hydrolysis and acidification (HA) process was applied to treating CS by adding LFD to the acidogenic reactor to improve microbial pre-decomposition and further solubilize recalcitrant organic polymers. Through combining the LFD and HA modification, the process was upgraded with associated improvement in anaerobic digestion (AD) performance. The variations of physico-chemical structure and AD performance of CS after LFD-HA compared with NaOH modification were analyzed. The results evidenced that LFD-HA promoted degradation of lignin monomer compounds from macromolecular polymers to aromatic compounds and acetic acid. The lignocellulosic structures and linkages were destroyed by hydroxy radical and hydrolytic enzyme. Compared with CS without pretreatment, the highest methane yield of LFD-HA CS was 265.1 mL·g −1 VS −1, and the digestion time (T80 ) was shortened by 27.8%. The populations of Methanobacteriaceae, Methanosarcinaceae and Ruminococcaceae were enriched during LFD-HA process. This research proposed that LFD-HA was an efficient and eco-friendly process in improving lignocellulose degradation and bio-methane generation from CS. Graphical abstract: Image 1 Highlights: Hydrolysis and acidification via liquid fraction of digestate strategy was studied. LFD-HA promoted the degradation of lignin monomer compounds. The highest biomethane yield of 265.1 mL g −1 VS −1 was achieved by LFD-HA. Ruminococcaceae were the predominant bacterium for LFD-HA.